Finite-Size Effects in Stochastic Models of Population Dynamics: Applications to Biomedicine and Biology - Di Patti, Francesca (Premio Tesi di Dottorato, 2010)
Population dynamics constitutes a widespread branch of investigations which finds important applications within the realm of life science. The classical deterministic (macroscopic) approach aims at characterizing the time evolution of families of homologous entities, so to unravel the global mechanisms which drive their dynamics. As opposed to this formulation, a microscopic level of modeling can be invoked which instead focuses on the explicit rules governing the interactions among individuals. A viable tool that enables to bridge the gap between the two approaches is the van Kampen's system size expansion. In this thesis we use this method to show how the finite-size effects accounted by the microscopic level might significantly alter the dynamics of biological phenomena.